Organising Support for Carers of Stroke Survivors (OSCARSS): a cluster randomised controlled trial with economic evaluation. Issue 1 (12th January 2021) - Patchwood, Emma; Woodward-Nutt, Kate; Rhodes, Sarah A; Batistatou, Evridiki; Camacho, Elizabeth; Knowles, Sarah; Darley, Sarah; Grande, Gunn; Ewing, Gail; Bowen, Audrey
Abstract : Objective: Investigated clinical effectiveness and cost-effectiveness of a person-centred intervention for informal carers/caregivers of stroke survivors. Design: Pragmatic cluster randomised controlled trial (cRCT) with economic and process evaluation. Setting: Clusters were services, from a UK voluntary sector specialist provider, delivering support primarily in the homes of stroke survivors and informal carers. Participants: Adult carers in participating clusters were referred to the study by cluster staff following initial support contact. Interventions: Intervention was the Carer Support Needs Assessment Tool for Stroke: a staff-facilitated, carer-led approach to help identify, prioritise and address the specific support needs of carers. It required at least one face-to-face support contact dedicated to carers, with reviews as required. Control was usual care, which included carer support (unstructured and variable). Outcome measures: Participants provided study entry and self-reported outcome data by postal questionnaires, 3 and 6 months after first contact by cluster staff. Primary outcome: 3-month caregiver strain (Family Appraisal of Caregiving Questionnaire, FACQ). Secondary outcomes: FACQ subscales of caregiver distress and positive appraisals of caregiving, mood (Hospital Anxiety and Depression Scale) and satisfaction with stroke services (Pound). The economic evaluation included self-reported healthcare utilisation, intervention costs and EQ-5D-5L. Randomisation and masking: Clusters were recruited before randomisation to intervention or control, with stratification for size of service. Cluster staff could not be masked as training was required for participation. Carer research participants provided self-reported outcome data unaware of allocation; they consented to follow-up data collection only. Results: Between 1 February 2017 and 31 July 2018, 35 randomised clusters (18 intervention; 17 control) recruited 414 cRCT carers (208 intervention; 206 control). Study entry characteristics were well balanced. Primary outcome measure: intention-to-treat analysis for 84% retained participants (175 intervention; 174 control) found mean (SD) FACQ carer strain at 3 months to be 3.11 (0.87) in the control group compared with 3.03 (0.90) in the intervention group, adjusted mean difference of −0.04 (95% CI −0.20 to 0.13). Secondary outcomes had similarly small differences and tight CIs. Sensitivity analyses suggested robust findings. Intervention fidelity was not achieved. Intervention-related group costs were marginally higher with no additional health benefit observed on EQ-5D-5L. No adverse events were related to the intervention. Conclusions: The intervention was not fully implemented in this pragmatic trial. As delivered, it conferred no clinical benefits and is unlikely to be cost-effective compared with usual care from a stroke specialist provider organisation. It remains unclear how best to support carers of stroke survivors. To overcome the implementation challenges of person-centred care in carers' research and service development, staff training and organisational support would need to be enhanced. Trial registration number: ISRCTN58414120 .